Association between history of viral infections and melanoma mortality - Nathan Shen; Polly Creveling; Joshua J. Horns; Josh Bleicher; John Hyngstrom; Tawnya Bowles; Michael Andreae; Tracy Onega; Elliot A. Asare (Heliyon)
Background: Viral infections (VIs) have been linked to T-cell exhaustion, a state that impacts the immune system's ability to mount an effective anti-tumor response. This immunosuppressive effect may potentially worsen outcomes in melanoma patients. This study investigates the relationship between a history of VIs and melanoma-specific mortality, with the goal of understanding whether prior history of Vis contribute to an increased risk of mortality in melanoma patients. Materials and methods: A retrospective review of patients in the Utah Population Database (1997–2020) was done. There were 17,754 eligible melanoma patients, with 2286 also having a history of viral infections. Multivariable Cox proportional hazard models were used to assess the effect of VI on melanoma-specific mortality. Results: History of VI was associated with a higher risk of melanoma-specific mortality (HR = 1.33, 95 % CI: 1.07–1.65, P = 0.01). No differences were observed in mortality among patients undergoing surgery and adjuvant immunotherapy. Conclusions: A history of viral infections was associated with higher melanoma-specific mortality. The mechanism of this association and relationship with different types of viral infections and duration of infections remain to be elucidated.